Mobile broadband multimedia networks techniques, models and tools for 4G - Correia, Luis M.; European Cooperation in the Field of Scientific and Technical Research (Organization) (Amsterdam ; London : Elsevier/Academic Press, 2006)
Mobile Broadband Multimedia Networks: Techniques, Models and Tools for 4th Generation Communication Networks provides the main results of the prestigious and well known European COST 273 research project on the development of next generation mobile and wireless communication systems. Based on the applied research of over 350 participants in academia and industry, this book focuses on the radio aspects of mobile and wireless broadband multimedia communications, by exploring and developing new methods, models, techniques, strategies and tools towards the implementation of 4th generation mobile and wireless communication systems. This complete reference includes topics ranging from transmission and signal processing techniques to antennas and diversity, ultra wide band, MIMO and reference scenarios for radio network simulation and evaluation. This book will be an ideal source of the latest developments in mobile multimedia broadband technologies for researchers, R & D engineers, graduates and engineers in industry implementing simulation models and conducting measurements. * Based on the well known and respected research of the COST 273 project Towards Mobile Broadband Multimedia Networks', whose previous models have been adopted by standardisation bodies such as ITU, ETSI and 3GPP * Gives methods, techniques, models and tools for developing 4th generation mobile and wireless communication systems * Includes the latest development of key technologies and methods such as MIMO systems, ultra wide-band and OFDM.
Preface -- List of contributors and editors -- List of acronyms -- 1 Introduction -- 2 Transmission techniques -- 3 Signal processing -- 4 Propagation modelling and channel characterisation -- 5 Antennas and diversity: from narrow band to ultra wide band -- 6 MIMO channel modelling -- 7 MIMO systems -- 8 Radio network aspects -- 9 UMTS radio networks -- Index.
"This book represents the research work of COST 273"--Pref.
Includes bibliographical references and index.
Keywords: Broadband communication systems; Wireless communication systems; Breedband; Multimedia; Electronic books